Guggenheim Museum Bilbao - Frank O. Gehry (Oz, 1996)
The Guggenheim Museum Bilbao, scheduled to be completed in 1997, is the result of a unique collaboration between the Basque County Administration, which finances and owns the project, and the Solomon R. Guggenheim Foundation, which will operate the Museum and provide the core art collection. The Museum represents the first step in the redevelopment of the former trade and warehouse district along the south bank of the Nervi on River.